Decolonizing Peace in Africa: Why African Traditions Hold a Key to Sustainable Peace? - (:unkn) unknown (My University, 2025)
Overview: The study on decolonizing peace highlights the critical role of African traditions in fostering peace by emphasizing indigenous approaches to conflict resolution, community cohesion, and restorative justice. Body of Knowledge: This study emphasizes the importance of embracing indigenous traditions and cultural practices as foundational elements for fostering sustainable peace in Africa. African traditions, rooted in communal values, restorative justice, and consensus-building, offer sustainable alternatives to Western-centric peace building models, which often overlook the continent's unique social, historical, and cultural contexts. Methods: The study was conducted in Lusaka district, the capital city of Zambia. The sample consisted 50 research participants. A purposive sampling technique was used to select key informants such as traditional chiefs, peace practitioners, academicians, and policymakers. Moreover, snowball sampling helped identify additional participants such as church leaders with relevant insights. The data collection process involved conducting semi-structured interviews and focus groups discussions (FGDs).The data collected were analyzed using study themes and content analysis. Results: The findings revealed that that African traditions, such as Ubuntu and communal consensus-building, foster inclusivity and a shared sense of responsibility, enabling communities to address conflicts collaboratively and restore relationships. Additionally, African peace building frameworks, rooted in collective decision-making, respect for elders, and culturally ingrained reconciliation practices, offer sustainable alternatives to Western-centric models that often overlook local contexts. Recommendation: Schools, universities, and civil society organizations should promote the communal values to cultivate a generation that prioritizes dialogue, cooperation, and collective well-being over adversarial approaches to conflict resolution.
Keywords: African Research